2020
DOI: 10.1021/acsami.0c18472
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Synthesis Using Single-Atom Catalysts Based on Two-Dimensional Organometallic Metal Phthalocyanine Monolayers under Ambient Conditions

Abstract: We have identified three novel metal phthalocyanine (MPc, M = Mo, Re, and Tc) single-atom catalyst candidates with excellent predicted performance for the production of ammonia from electrocatalytic nitrogen reduction reaction (NRR) through a combination of high-throughput screening and first-principles calculations on a series of 3d, 4d, and 5d transition metals anchored onto extended Pc monolayer catalysts. Analysis of the energy band structures and projected density of states of N 2 -MPc revealed significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
92
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 59 publications
2
92
0
Order By: Relevance
“…For instance, Yang et al performed the DFT highthroughput screening of catalysts for NRR among a series of transition metal atoms supported on phthalocyanine or borophene monolayer, which provided insights to rational design and explore the efficient and stable NRR catalysts. [403,406] In particular, the NRR reaction (N 2 + 6H + + 6e − → 2NH 3 ) involves several intermediates (*N 2 H, *N 2 H 2 , *N 2 H 3 , *NH 2 , and *N) with two potential reaction pathways (Figure 11b). One is the dissociative pathway, in which the first step is N 2 dissociates into two separate N atoms before the hydrogenation.…”
Section: Nitrogen Reduction Reactionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Yang et al performed the DFT highthroughput screening of catalysts for NRR among a series of transition metal atoms supported on phthalocyanine or borophene monolayer, which provided insights to rational design and explore the efficient and stable NRR catalysts. [403,406] In particular, the NRR reaction (N 2 + 6H + + 6e − → 2NH 3 ) involves several intermediates (*N 2 H, *N 2 H 2 , *N 2 H 3 , *NH 2 , and *N) with two potential reaction pathways (Figure 11b). One is the dissociative pathway, in which the first step is N 2 dissociates into two separate N atoms before the hydrogenation.…”
Section: Nitrogen Reduction Reactionmentioning
confidence: 99%
“…[242] It has been proposed that the first protonation of *N 2 to from *N 2 H is the potential limiting step on catalysts with weakly nitrogen-binding capability (Figure 11c), while the most difficult step is suggested to be the reduction of *NH 2 to NH 3 or the protonation of *NH to form *NH 2 on catalysts with strong nitrogen binding (Figure 11d). [367,403,407] Moreover, the HER reaction is a competing reaction, decreasing the faradaic efficiency for NRR. Some studies demonstrated that NRR at more negative potentials (−1 to −1.5 V) will dominate over HER because of stronger nitrogen binding on the active site than that of H. [408]…”
Section: Nitrogen Reduction Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the concept of single-atom catalysis was firstly proposed by Zhang, Li, Liu et al in 2011 [1], considerable attention has been paid to this area because of its unique homogeneous structural characteristics of a single-atom (SA) active center and the excellent catalytic performance in heterogeneous catalysis [2][3][4][5][6][7][8][9][10]. Several reviews [11][12][13][14][15] have summarized the development of single-atom catalysts (SACs), the structure-function relationship between SACs and their catalytic performance, and the diverse applications of SACs in heterogeneous catalysis [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce pollution, one of the technologies adopted by most coal-red power plants is selective catalytic reduction denitration, and the core of the SCR technology is the catalyst. [2][3][4][5] Although some progress has been made in the study of SCR catalysts, the denitration catalyst is expensive and its sulfur resistance is insufficient. [6][7][8][9] Consequently, the preparation of high performance denitration and sulfur-resistant catalysts characterized by high efficiency, simplicity, and energy conservation has become a hot topic in this eld.…”
Section: Introductionmentioning
confidence: 99%